The effects of rest interval and resistance training on quadriceps femoris muscle: Part II: EMG and perceived exertion - Pincivero, D. M.; Campy, R. M.; Karunakara, R. G. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The purpose of this study was to examine the effects of rest interval on quadriceps femoris muscle activation and perceived exertion, during short-term resistance training. METHODS: Vastus medialis (VM) and vastus lateralis (VL) muscle electromyograms (EMG) were assessed in 15 males during a sustained 80 % maximal voluntary contraction (MVC). During the pre-training evaluation, the absolute value of the 80 % MVC (N.m) and contraction duration (s) was performed at 2, 4, and 6 weeks during the training period. Perceived exertion was measured via the Borg category-ratio scale every 5 s during the 80 % MVC. Subjects were randomly assigned to 3 groups: group 1 received a 40 s rest interval in between exercise sets, group 2 received a rest period of 160 s, and the control group did not participate in training. Groups 1 and 2 performed isokinetic knee extensions at 180 deg.s(-1) 2 days per week for 6 weeks. RESULTS: The results demonstrated a significant decrease in VM EMG within the initial portion of the 80 % MVC across the training period in the short rest interval group. The long rest interval and control groups showed no significant changes in VM EMG during 1st part of the contraction across the training period, whereas the control group exhibited a significant reduction in VL EMG across weeks 4 to 6. VL EMG increased during the 80 % MVC in the control group across the training period. VM EMG increased during the sustained contractions in the long rest interval and control groups across the training period. The perceived exertion response was lower in the 1st part of the 80 % MVC in the short and long rest interval groups, but not in the control group, across the training period. The results also showed a significant decrease in perceived exertion at the end of the sustained contraction in the short rest interval group, but not in the long rest interval group or the control group. CONCLUSIONS: The findings from this study suggest that the application of relatively short rest intervals in between sets of resistance exercise induced a greater neuromuscular response of the VM muscle during short-term training.